Bacterial Profile of Urinary Tract - BABA-MOUSSA, LAMINE SAÏD; BANKOLE, HONORÉ SOUROU; DOUGNON, T. VICTORIEN (My University, 2016)
Urinary tract infections remain the most common bacterial infection in human population. They are also one of the most frequently occurring nosocomial infections, representing about 40% of all nosocomial bacterial infections world widely and associated with important medical and financial implications. This retrospective study aimed to establish the bacterial profile of UTIs in Benin. Therefore, reported data were collected from 2003 to 2012 at Menontin’s Hospital in Cotonou and subjected to analyses. At the end of the study, fourteen different bacteria species were found to be associated with UTI cases in Benin. Escherichia coli was the most prevalent followed by Staphylococcus aureus. Results of the current study are helpful to the health care community of Benin in establishing the appropriate antibiotherapy for UTI patients’ treatment with respect organisms into circulation.
Keywords: Bacteria; UTIs; Public Health